Health Information Media for Outpatient Services at Puskesmas OPI Palembang Based on a Website - Salsabilah, Engga; Megawaty; Fatoni; Amalia, Rahayu (International Journal Software Engineering and Computer Science (IJSECS), 2024)
The advancement of information technology has significantly influenced various aspects of life, especially in the delivery of healthcare services. Websites now play a pivotal role in providing healthcare services and information to patients, acting as a vital medium of communication. Puskesmas OPI Palembang is a healthcare institution serving the community, consisting of several departments (polyclinics), including the Maternal and Child Health Room, the Elderly Room, Special Room 1 for Respiratory Diseases, Special Room 2, General Examination Room, Dental and Oral Room, Laboratory Room, Pediatric Room, and Immunization Room. At Puskesmas OPI Palembang, a blog is currently the primary medium for disseminating health service information, alongside brochures, e-flyers, and promotional materials distributed to the local community through free health education initiatives. For outpatient health services, patient registration is still managed using paper-based records. To improve services, a website has been developed to serve as an effective platform for patients to access information about the health center, doctor schedules, polyclinics, and outpatient services, including patient registration. The website provides essential details such as the health center's location, contact information, and doctor schedules, including names, working hours, and practice days. Patients can register online by completing personal information, complaints, preferred polyclinic, and doctor details. The website was developed following the Planning, Design, Coding, and Testing phases of the Extreme Programming methodology.